Synthesis of Composite Graphene/ Fe3O4 by Electrophoretic Deposition Using Pulse Direct Current - Ervina Rumpakwakra; Hariyati Purwaningsih; Widiyastuti Widiyastuti; Heru Setyawan (IPTEK Journal of Proceedings Series, 2020)
Composites Graphene/Fe3O4 have been successfully synthesized by the electrophoretic deposition method using pulse direct current (PDC) on a nickel foam substrate. In this study, we synthesized graphene and Fe3O4 separately before the two materials were composited. We synthesize graphene from coconut shell charcoal and synthesize Fe3O4 from pure iron. Graphene and Fe3O4 which have been formed, are dissolved with demineralized water as a dispersing medium so that a solution of 1.5 mg / mL is obtained which is then compiled layer by layer on the surface of the substrate with variations in deposition time of 10 to 30 minutes at room temperature. This aims to determine the effect of deposition time on the formation of graphene/Fe3O4 composites. The results showed that the use of PDC was able to precipitate graphene/Fe3O4 composites on the surface of the substrate. The use of longer deposition time, results in more graphene/Fe3O4 composites which adhere to the substrate surface. This result is also supported by XRD testing which shows the longer the deposition time, the diffraction peaks appear sharper.